Analysis of the Influence of Program Quality, Production, and Broadcast Reach on the Increase of PNBP LPP RRI Tolitoli Station: Analisis Pengaruh Kualitas Program, Produksi, dan Jangkauan Siaran terhadap Peningkatan PNBP LPP RRI Stasiun Tolitoli - Moh. Rasyid; Dwiyanti S. Parman; Edi Yanto (International Journal of Economic Entrepreneurship and Business Management, 2025)
This study aims to analyze the influence of program quality, production quality, and broadcast reach on increasing Non-Tax State Revenue (PNBP) of the Public Broadcasting Institution of Radio of the Republic of Indonesia (LPP RRI) Tolitoli Station. The method used is a quantitative approach with primary data sources obtained through interviews, observations, and questionnaires. Data analysis was carried out by statistical test using SPSS version 26 application. The results showed that partially the quality of the program had a significant effect on the increase in PNBP (Sig. 0.002 < 0.05; t count 2.724 > t table 2.011). Production quality was also shown to have a significant effect (Sig. 0.000 < 0.05; t count 3.298 > t table 2.011), as well as broadcast coverage (Sig. 0.000 < 0.05; t count 2.981 > t table 2.011). Simultaneously, these three variables have a significant influence on the increase in the RRI PNBP of Tolitoli Station (Sig. 0.000 < 0.05; F calculates 8.043 > F table 2.84). These findings confirm that improving program quality, optimizing production, and expanding broadcast coverage are strategic factors in supporting LPP RRI's financial performance, especially in contributing to non-tax state revenue.